An Exploratory Investigation of Gender and Cross-Major Differences in Business Student Success in an IT Course. - Taowen Le; Jin Zhang; Wayne Wei Huang (Journal of the Utah Academy of Sciences, Arts & Letters, 2015)
As information technology (IT) knowledge and skills become more and more essential to the success of modern business world, business students' future success is inevitably impacted by their ability to learn and master relevant IT. This study investigated whether male and female students would have the same potential for success in an IT- intensive business world, whether students of various business majors might enjoy the same level of success in an IT-sustained business environment, and whether special measures are necessary to ensure a proper preparation for all business students. Employing a variety of quantitative research methods (T-tests, ANOVA tests, post-hoc tests, and mean plots) and administering one comprehensive MS Access project, one comprehensive MS Excel project, eight timed quizzes, and three timed exams, this study monitored and analyzed academic performances of over 190 business students in an IT course offered at a major public university in the U.S. across two academic years. The study specifically investigated potential gender differences and potential cross-major differences in business student success in an IT course. While male students seemed to have achieved slightly higher performance scores on the MS Access project and exams, female students seemed to have achieved slightly higher scores on the MS Excel project, quizzes, and overall performance. Except a small difference on exams, however, none of the other differences was statistically significant. While average performance scores seemed to differ across seven different major groups (Accounting, Business Management, Finance, Human Resource Management, Marketing, Supply Chain Management, Other[non-business]) on MS Access project, MS Excel project, quizzes, exams, and overall performance, almost all such differences were statistically insignificant with two exceptions: (1) On the MS Access project, students with Accounting, Business Administration, Finance, and Supply Chain Management majors performed better than students of Other (non-business) majors; and students with a Supply Chain Management major performed better than students with a Marketing major; and (2) On quizzes, Accounting students performed better than students of Finance, Marketing, and Supply Chain Management; and students of Business Administration and Other (non-business) majors performed better than students of Supply Chain Management major.